2017
DOI: 10.1186/s13049-017-0450-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of intrathoracic pressure regulation therapy in breathing patients for the treatment of hypotension secondary to trauma

Abstract: BackgroundIntrathoracic pressure regulation (IPR) therapy has been shown to increase blood pressure in hypotensive patients. The potential value of this therapy in patients with hypotension secondary to trauma with bleeding is not well understood. We hypothesized that IPR would non-invasively and safely enhance blood pressure in spontaneously breathing patients with trauma-induced hypotension.MethodsThis prospective observational cohort study assessed vital signs from hypotensive patients with a systolic blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These studies demonstrated that spontaneous breathing against inspiratory resistance increased during progressive central hypovolemia (22,63,66), an outcome that was associated with increased stroke volume (66), cardiac output (66), arterial blood pressure (22,66), and improved cerebral blood flow dynamics with delayed symptoms (63). When translated to the treatment of more than 250 hypotensive patients in studies conducted at independent sites during prehospital transport, average blood pressure increased from 80/50 mmHg to~100/65 mmHg with a 47% increase in pulse pressure and improved feelings of well-being reported in Ͼ85% of the patients (10,11,44,70,78,79). When applied to 20 normovolemic anesthetized patients who underwent coronary artery bypass graft before sternotomy, inspiratory resistance caused cardiac output to increase by Ͼ12% while maintaining arterial blood pressure (34).…”
Section: Translation To Medical Care In Human Pathophysiologymentioning
confidence: 99%
“…These studies demonstrated that spontaneous breathing against inspiratory resistance increased during progressive central hypovolemia (22,63,66), an outcome that was associated with increased stroke volume (66), cardiac output (66), arterial blood pressure (22,66), and improved cerebral blood flow dynamics with delayed symptoms (63). When translated to the treatment of more than 250 hypotensive patients in studies conducted at independent sites during prehospital transport, average blood pressure increased from 80/50 mmHg to~100/65 mmHg with a 47% increase in pulse pressure and improved feelings of well-being reported in Ͼ85% of the patients (10,11,44,70,78,79). When applied to 20 normovolemic anesthetized patients who underwent coronary artery bypass graft before sternotomy, inspiratory resistance caused cardiac output to increase by Ͼ12% while maintaining arterial blood pressure (34).…”
Section: Translation To Medical Care In Human Pathophysiologymentioning
confidence: 99%
“…Intraoperative hypercarbia was largely due to CO 2 insufflation and was treated by hyperventilation. Some studies have reported that infants who undergo thoracoscopic surgery are more likely to develop hypercapnia (19). Sevoflurane (0.5-1.0 MAC) and an intravenous infusion of remifentanil (0.2-0.3 mg /kg/min) were used to maintain general anesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…Although human experimental evidence for enhancing cerebral perfusion with IPR therapy is compelling, translation to clinical use is essential. In this regard, IPR therapy application for the treatment of all-cause hypotension in a civilian prehospital setting resulted in elevation of ABP from approximately 80/45 mm Hg to approximately 100/60 mm Hg with amelioration of symptoms 22,36 . It is important to note that elevated ABP elicited by IPR therapy in spontaneously breathing trauma patients with hemorrhage remained in a hypotensive level with no evidence of increased bleeding 36 …”
Section: Clinical Evidence For Treating Tbi With Ipr Therapymentioning
confidence: 97%
“…In this regard, IPR therapy application for the treatment of all-cause hypotension in a civilian prehospital setting resulted in elevation of ABP from approximately 80/45 mm Hg to approximately 100/60 mm Hg with amelioration of symptoms. 22,36 It is important to note that elevated ABP elicited by IPR therapy in spontaneously breathing trauma patients with hemorrhage remained in a hypotensive level with no evidence of increased bleeding. 36 Although elevated ABP reported in hypotensive patients using IPR therapy is encouraging for treatment of TBI, measurements of cerebral hemodynamics are rare.…”
Section: Clinical Evidence For Treating Tbi With Ipr Therapymentioning
confidence: 99%
See 1 more Smart Citation